Heroism and Gender in War Films - Ritzenhoff, Karen A. author. aut Link
XV, 271 p. 13 illus.
Keywords: Filmic constructions of war heroism have a profound impact on public perceptions of conflicts. Here, contributors examine the ways motifs of gender and heroism in war films are used to justify ideological positions, shape the understanding of the military conflicts, support political agendas and institutions, and influence collective memory.